Mechanistic-empirical pavement design guide : a manual of practice. (American Association of State Highway and Transportation Officials, 2020)
This 2020 3rd edition includes the following revisions and updates from the previous 2015 2nd edition: new fracture mechanics-based model for reflective cracking in AC overlays over flexible, semi-rigid, and rigid pavements; new mechanistic-empirical model for short jointed plain concrete pavement (SJPCP) overlays of flexible pavements; new flexible and semi-rigid pavement global calibration coefficients; addition of non-structural preventative maintenance treatment consideration for flexible and rigid pavements; addition of five level 3 default distributions for normalized axle load spectra (NALS); updated climate discussion for Modern Era Retrospective Reanalysis (MERRA) and North American Regional Reanalysis (NARR) data; incorporation of crack load transfer efficiency (LTE) for flexible pavements; expanded guidance for creep compliance and indirect tensile strength inputs for asphalt wearing surface layers; and updated standards references.